(3GdOQ Gdcejf HPjd GdYbO GdKejf aj JGQjN GdHdO GdCejf dJbi GdOjf GdaGSis - (3fLe GdOjf CHi GdbGSe eMeO GdeOYh YeQ Hf eMeO Hf eMeO Hf eMeO Hf agO GdgGTei Gdecj GdTGaYjs; (3GHf agO , YeQ Hf eMeO Hf eMeO Hf CHj GdNjQ eMeO Hf eMeO Hf YHO Gddg Hf agO GdbQTj GdgGTej, CHj GdNjQ , fLe GdOjf,J (B885 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCRdi GdQMje GdCHOi s
(3LYdg PjdkG Ydi GdYbO GdKejf ddaGSis
(3fbdkG Yf fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
Keywords: (3GdJGQjNs